Strategies of a horticulturist family from Bolivia in the Santa Rosa-Toay metropolitan area (La Pampa, Argentina) (Huellas, 2023)
The aim of this paper is to reconstruct the social reproduction strategies of a horticulturist family from Bolivia in the Santa Rosa-Toay metropolitan area. A particular territoriality is present in a context where obstacles, opportunities, global processes and local singularities coexist for the development of this productive and domestic unit that seeks to obtain capital (conceptually classified by Pierre Bourdieu as economic, cultural, social and symbolic). At the same time, the social practices analyzed have characteristics of family farming and demonstrate their potential to contribute to the achievement of food sovereignty. Likewise, the periurban area selected in the center of Argentina, an edge space subjected to significant transformations caused by the capitalist system, also has its correlation in the adopted strategies. In this way, the space-time aspect includes the Santa Rosa-Toay metropolitan area, between the years 2002 and 2022. The qualitative methodology is chosen for its interpretative nature of the complex social world. In addition, dialogues are established between various theoretical contributions, what is observed and information from in-depth interviews, cartography, news, documentaries and data from governmental agencies.
Keywords: strategies; territoriality; horticulture; Bolivia; food sovereignty